Exploring Educational Media on Indonesian Studies for Third-Culture Kids' Identity Development - Hefira, Vania (Universitas Multimedia Nusantara, 2024)
Indonesian Generation Z faces challenge in strengthening their national identity because of globalization. This is an urgency as Indonesia is progressing towards